PENINGKATAN AKTIFITAS DAN HASIL BELAJAR DENGAN MENERAPKAN MODEL PEMBELAJARAN THINK PAIR SHARE - Maspito, Maspito (JURNAL GLOBAL EDUKASI, 2018)
Abstract: Problems that exist in class VIA of SMP Negeri 3 Tapung Hilir is whether using the Think Pair Share model can improve student learning activities and outcomes on social studies subjects in the VIIA class of SMP Negeri 3 Tapung Hilir Academic Year 2016/2017. In general, the mastery of social knowledge of basic education graduates is relatively sufficient, but the mastery of values in terms of the application of values, social skills and social participation results are not encouraging. These weaknesses are certainly related or motivated by many things, especially the education or learning process, the managers and their implementation as well as influential factors. Therefore the teacher must be able to choose a learning model that can foster interactive, sense of togetherness, namely with the cooperative learning model. The activity of students who get the very good category in the first cycle is 23.33% in the second cycle to 53.33%, the group work is very good in the first cycle 20.00% in the second cycle becomes 56.67% and the average value increases the cycle I 65.75 to 89.15 in the second cycle, as well as the learning completeness aspects from 40% in the first cycle to 90% in the second cycle. From these data show that by using the Think Pair Share model can improve the activities and student learning outcomes so that this learning model can be applied by other social studies teachers in teaching and learning activities. Keywords: Learning Activities and Results Abstrak: Permasalahan yang ada di kelas VIIA SMP Negeri 3 Tapung Hilir adalah Apakah dengan menggunakan model Think Pair Share dapat meningkatkan aktifitas dan hasil belajar siswa pada mata pelajaran IPS di kelas VIIA SMP Negeri 3 Tapung Hilir Tahun Pelajaran 2016/2017. Secara umum penguasaan pengetahuan sosial lulusan pendidikan dasar relatif cukup, tetapi penguasaan nilai dalam arti penerapan nilai, ketrampilan sosial dan partisipasi sosial hasilnya belum menggembirakan. Kelemahan tersebut sudah tentu terkait atau dilatarbelakangi oleh banyak hal, terutama proses pendidikan atau pembelajarannya, para pengelola dan pelaksanaannya serta faktor- faktor yang berpengaruh. Oleh karena itu guru harus bisa memilih model pembelajaran yang bisa menumbuhkan interaktif, rasa kebersamaan yaitu dengan model pembelajaran koopertaif. Aktivitas siswa yang mendapat kategori amat baik siklus I 23,33% pada siklus II menjadi 53,33%, kerja kelompok kategori amat baik siklus I 20,00% pada siklus II menjadi 56,67% dan rat-rata nilai meningkat siklus I 65,75 menjadi 89,15 pada siklus II, serta pada aspek ketuntasan belajara dari 40% pada siklus I menjadi 90% pada siklus II. Dari data tersebut menunjukkan bahwa dengan menggunkan model Think Pair Share dapat meningkatkan aktivitas dan hasil belajar siswa sehingga model pembelajaran ini dapat diterapkan oleh guru IPS yang lain dalam kegiatan belajar mengajar. Kata kunci: Aktifitas Dan Hasil Belajar, Think Pair Share